2008
DOI: 10.1111/j.1469-8986.2008.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular dynamics in blood phobia: Evidence for a key role of sympathetic activity in vulnerability to syncope

Abstract: This study was aimed at clarifying the mechanism predisposing people with blood phobia to syncope by investigating the complete hemodynamic response pattern and the underlying autonomic control. Blood phobics and controls were shown 3 film-clips: phobia-related, phobia-unrelated, and neutral. Hemodynamic responses were recorded using impedance cardiography and Finapres. Preejection period and respiratory sinus arrhythmia were employed as indices of cardiac sympathetic and parasympathetic activity. Self-ratings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 45 publications
5
40
0
2
Order By: Relevance
“…It has been proposed that the absence of a defence response in BII phobics exposed to their fear stimuli may be explained by a dysregulation of the sympathetic activity, especially in the cardiovascular system (e.g., Sarlo et al, 2008) as well as in other response systems, like skin conductance (e.g., Hamm et al, 1997). Our data are compatible with this hypothesis, since the unconscious perception of the feared pictures did not result in an increase of their sympathetically mediated SCRs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It has been proposed that the absence of a defence response in BII phobics exposed to their fear stimuli may be explained by a dysregulation of the sympathetic activity, especially in the cardiovascular system (e.g., Sarlo et al, 2008) as well as in other response systems, like skin conductance (e.g., Hamm et al, 1997). Our data are compatible with this hypothesis, since the unconscious perception of the feared pictures did not result in an increase of their sympathetically mediated SCRs.…”
Section: Discussionsupporting
confidence: 91%
“…For example, while some researchers have found HR deceleration when BII phobics are exposed to blood-related stimuli, like pictures (e.g., Hamm et al, 1997), other authors, using longer exposures, like surgery film-clips, have found an initial HR acceleration (during the first 66 seconds of exposure) followed by a diminution of the HR, that falls under baseline (i.e., deceleration) at the end of the exposure, (e.g., Sarlo et al, 2002). Other studies have only found HR acceleration when BII subjects are exposed to blood-related film-clips, but accompanied by a marked fall in systolic blood pressure (Sarlo et al, 2008). As proposed by these authors, the dysfunctional cardiovascular reaction observed in BII phobics would depend more on the involvement of the sympathetic system, rather than the parasympathetic system.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Despite the implication of a predominant role of parasympathetic activity in the traditional term, vasovagal response, the importance of sympathetic withdrawal has been acknowledged for many years and is related to common use of the alternative term, vasodepressor response [40][41][42][43]. In a recent laboratory study of blood phobics' responses to a film depicting surgery, Sarlo et al [44] observed a pattern of results somewhat similar to those of the present study. That is, the phobics had an increase in CO during the surgery film but a decrease in TPR, which may be a primary reason for their susceptibility to fainting in such circumstances.…”
Section: The Typical Response To Blood Donationsupporting
confidence: 87%
“…In this case, a certain degree of BP elevation corresponding to the strength of mental stress has to be almost always sought by the central nervous system. The only exception to this, to the present authors' knowledge, is the observation of marked decline in systolic BP that occurred in blood phobics during viewings of phobia-related films [25].…”
Section: Discussionmentioning
confidence: 78%